2018
DOI: 10.1038/s41419-018-1035-6
|View full text |Cite
|
Sign up to set email alerts
|

The induction and consequences of Influenza A virus-induced cell death

Abstract: Infection with Influenza A virus (IAV) causes significant cell death within the upper and lower respiratory tract and lung parenchyma. In severe infections, high levels of cell death can exacerbate inflammation and comprise the integrity of the epithelial cell barrier leading to respiratory failure. IAV infection of airway and alveolar epithelial cells promotes immune cell infiltration into the lung and therefore, immune cell types such as macrophages, monocytes and neutrophils are readily exposed to IAV and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 111 publications
(180 reference statements)
3
88
0
1
Order By: Relevance
“…This acute inflammation in response to influenza infection is mediated by lung monocytes and monocytederived dendritic cells that are involved in the detection and clearance of influenza virus and influenza pathogenesis in the lungs [80]. These innate immune cells are not only susceptible to influenza-induced apoptotic and necrotic cell death [81], influenza infection has a direct effect on monocytes which results in the downregulation of Th17-mediated immunity necessary for protection against secondary pneumococcal pneumonia [82]. This effect of influenza infection on the monocyte function necessary for the clearance of pneumococcus has recently been demonstrated in a human challenge model [83].…”
Section: Role Of Innate Immune Cells In Influenza Infectionmentioning
confidence: 99%
“…This acute inflammation in response to influenza infection is mediated by lung monocytes and monocytederived dendritic cells that are involved in the detection and clearance of influenza virus and influenza pathogenesis in the lungs [80]. These innate immune cells are not only susceptible to influenza-induced apoptotic and necrotic cell death [81], influenza infection has a direct effect on monocytes which results in the downregulation of Th17-mediated immunity necessary for protection against secondary pneumococcal pneumonia [82]. This effect of influenza infection on the monocyte function necessary for the clearance of pneumococcus has recently been demonstrated in a human challenge model [83].…”
Section: Role Of Innate Immune Cells In Influenza Infectionmentioning
confidence: 99%
“…Therefore, the numbers of neutrophils at the infected lungs must be tightly tuned to maximize efficient viral clearance while minimizing immunopathology (10). In such settings, the initiation of neutrophil apoptosis and consequent reduction in neutrophil numbers may be advantageous to limit lung inflammation and bystander tissue injury (11). To this end, however, a direct link between excess neutrophil recruitment and/or survival and the extent of pulmonary inflammation during IAV infection remains unclear.…”
mentioning
confidence: 99%
“…An alternative explanation comes from our Calu-3 model, in which we found that MIF increases cellular necrosis or delayed clearance of apoptotic cells during late stages of IAV infection and enhances viral replication. This may explain MIF's ability to enhance viral replication, as cells exhibiting increased late apoptotic and necrotic characteristics during late stages of infection have been a marker of enhanced IAV propagation (38,40).…”
Section: Discussionmentioning
confidence: 99%